Positive role of the MHC Class-I antigen presentation regulator m04/gp34 of murine cytomegalovirus in antiviral protection by CD8 T cells - Becker, Sara; Fink, Annette (Frontiers in Cellular and Infection Microbiology, 2020)
Murine cytomegalovirus (mCMV) codes for MHC class-I trafficking modulators m04/gp34, m06/gp48 and m152/gp40. By interacting with the MHC class-Iα chain, these proteins disconnect peptide-loaded MHC class-I (pMHC-I) complexes from the constitutive vesicular flow to the cell surface. Based on the assumption that all three inhibit antigen presentation, and thus the recognition of infected cells by CD8 T cells, they were referred to as ‘immunoevasins’. Improved antigen presentation mediated by m04 in the presence of m152 after infection with deletion mutant mCMV-Δm06W, compared to mCMV-Δm04m06 expressing only m152, led us to propose renaming these molecules ‘viral regulators of antigen presentation’ (vRAP) to account for both negative and positive functions. In accordance with a positive function, m04-pMHC-I complexes were found to be displayed on the cell surface, where they are primarily known as ligands for Ly49 family natural killer (NK) cell receptors. Besides the established role of m04 in NK cell silencing or activation, an anti-immunoevasive function by activation of CD8 T cells is conceivable, because the binding site of m04 to MHC class-Iα appears not to mask the peptide binding site for T-cell receptor recognition. However, functional evidence was based on mCMV-Δm06W, a virus of recently doubted authenticity. Here we show that mCMV-Δm06W actually represents a mixture of an authentic m06 deletion mutant and a mutant with an accidental additional deletion of a genome region encompassing also gene m152. Reanalysis of previously published experiments for the authentic mutant in the mixture confirms the previously concluded positive vRAP function of m04.
Gesehen am 25.11.2020